(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Children’s fear, as a culturally and socially mediated emotion, is constructed and communicated through language rather than existing as a purely psychological state. This study examines the linguistic encoding of childhood fear in two nineteenth-century realist novels: Hamza Hakimzoda Niyoziy’s Zaharli hayot (1915) and Charles Dickens’s Oliver Twist (1838). Using a qualitative, lexico-semantic and stylistic approach, the research analyzes fear-related vocabulary, idiomatic expressions, metaphorical patterns, and narrative voice in passages depicting children’s vulnerability and anxiety. The corpus includes episodes of emotional and physical threat, social humiliation, corporal punishment, and moral intimidation. Findings show that the Uzbek text foregrounds fear as a response to authoritarian domestic structures and patriarchal discipline, often realized through verbs of trembling, hesitation, and internal struggle, such as hayiqmoq, qo‘rqib ketdi, and vijdoni qiynaldi. In contrast, Dickens’s novel frames fear through external social dangers — poverty, criminal exploitation, and institutional cruelty — represented with expressive emotional lexicon (trembled, terrified, shuddering, pale with fear) and atmospheric imagery of darkness and confinement. Both texts reveal that linguistic mechanisms — metaphor, repetition, evaluative adjectives, and embodied verbs — shape the child’s emotional reality. The study demonstrates that children’s fear in nineteenth-century literature is not merely narrated but linguistically constructed through culturally specific discourse strategies, contributing to cross-cultural stylistics and emotion linguistics.